Speaking Challenges of High and Low Achieving EFL Students in Indonesian Pesantren: A Comparative Study - Dhian Marita Sari (Lembaga Pendidikan Hikmatun Najah Blora, 2025)
This comparative qualitative study explores the English-speaking challenges experienced by high- and low-achieving EFL students in an Indonesian pesantren context. Twelve female students were purposively selectedsix high-achievers and six low-achievers based on academic records and teacher input. Data were gathered through semi-structured interviews and analyzed thematically. The findings reveal that high-achieving students encounter affective and environmental barriers, whereas low-achieving students are constrained by linguistic deficits and motivational issues. Students proposed strategies including self-talk, digital tools, and institutional support to overcome these difficulties. The study highlights the need for differentiated pedagogy and contextualized support in pesantren-based EFL programs.